2013
DOI: 10.1371/journal.pone.0082376
|View full text |Cite
|
Sign up to set email alerts
|

Immunomagnetic Separation Combined with Polymerase Chain Reaction for the Detection of Alicyclobacillus acidoterrestris in Apple Juice

Abstract: A combination of immunomagnetic separation (IMS) and polymerase chain reaction (PCR) was used to detect Alicyclobacillus acidoterrestris (A. acidoterrestris) in apple juice. The optimum technological parameters of the IMS system were investigated. The results indicated that the immunocapture reactions could be finished in 60 min and the quantity of IMPs used for IMS was 2.5 mg/mL. Then the combined IMS-PCR procedure was assessed by detecting A. acidoterrestris in apple juice samples. The agarose gel electropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 27 publications
(37 reference statements)
2
16
0
Order By: Relevance
“…Antibody attached to solid surface can capture bacteria through attachment to cell surface proteins and allow specific isolation of the bacteria from samples with high background flora [8]. IC can be used in combination with culture or molecular methods for isolation and detection of the pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody attached to solid surface can capture bacteria through attachment to cell surface proteins and allow specific isolation of the bacteria from samples with high background flora [8]. IC can be used in combination with culture or molecular methods for isolation and detection of the pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…are non-pathogenic, thermo-acidophilic and spore-forming bacteria. The spores can not only survive the pasteurization procedure normally applied to fruit juices and beverages, but also germinate and proliferate in acidic products (Wang et al, 2013). Since the first case of apple juice spoilage linked to Alicyclobacillus acidoterrestris in 1984, Alicyclobacillus-related contamination has been reported in various juices, juice blends, juice concentrates and carbonated fruit drinks (Smit et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ten out of 13 samples (77%) showed background contamination of the genus Alicyclobacillus, while 7 out of the 13 samples (54%) showed the specific presence of A. acidoterrestris background contamination (Table 1). A number of reports have shown that A. acidoterrestris can be present in both fresh juices and juice concentrates (Pettipher et al 1997;Luo et al, 2004;Groenewald et al 2009;Groenewald et al 2013;McKnight et al, 2010;Wang et al, 2013). The presence of background Alicyclobacillus spp.…”
Section: Resultsmentioning
confidence: 99%
“…We tested 13 different retail store purchased fruit juice and puree matrices (varying in soluble solids content) that were spiked in the laboratory with low levels (10 CFU/ml) of A. acidoterresteris spores. Previous studies have employed higher inoculation concentrations such as 10 4 CFU/ml and 10 5 CFU/ml (Yamazaki et al, 2008;Wang et al, 2013, (Funes-Huacca et al, Funes-huacca et al 2004). We chose this low level since a previous study suggested that A. acidoterrestris contamination concentrations in US juices could be low (Pettipher et al, 1997).…”
Section: Introductionmentioning
confidence: 99%